Considerations on methodology used in the World Health Organization 2000 Report - Ugá Alicia Domingues; Almeida Célia Maria de; Szwarcwald Célia Landmann; Travassos Cláudia; Viacava Francisco; Ribeiro José Mendes; Costa Nilson do Rosário; Buss Paulo Marchiori; Porto Silvia (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
The article analyzes the World Health Organization Report for 2000, with emphasis placed on the methodology used to analyze the indicators utilized to compare and classify the performance of the health systems of the 191 member countries. The Report's contribution was the compromise of monitoring the performance of the health systems of member countries, but because of the inconsistent way it was elaborated, and the utilization of questionable scientific evaluation methodologies, the Report fails to give a clear picture. A criterion-based methodology revision is imposed. The main problems in evidence are the choice of individual indicators of disparity in health that discount the population profile, the inadequate control of the impact of social disparities over the performance of the systems, the evaluation of the responsibility of systems that are only partially articulated to the right of the citizens, the lack of data for a great number of countries, consequently having inconsistent estimations, and the lack of transparency in the methodological procedures in the calculation of some indicators. The article suggests a wide methodological revision of the Report.